2018
DOI: 10.3892/etm.2018.6443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutamine on cytokines 1L‑1 and TNF‑α in rehabilitation and prognosis of patients with lobectomy

Abstract: This study was designed to investigate the effects of glutamine on cytokines 1L-1, TNF-α and prognosis of patients with lobectomy in the process of postoperative rehabilitation. A total of 78 patients with lung cancer who underwent lobectomy from January 2015 to January 2017 were selected in Daqing Oilfield General Hospital (Daqing, China). Patients were randomly divided into two groups, 39 patients in each group. Patients in the control group were treated with conventional treatment, while patients in the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Arginine supplementation only showed that topical administration did not affect IL-10 production in mice with laparotomy ( Jeronimo et al , 2016 ). In Contrary, several studies showed that glutamine only affects the high production of IL-10 in lobectomy patients ( Wang et al , 2018 ) and in bone marrow-derived macrophages induced by LPS ( de Oliveira et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine supplementation only showed that topical administration did not affect IL-10 production in mice with laparotomy ( Jeronimo et al , 2016 ). In Contrary, several studies showed that glutamine only affects the high production of IL-10 in lobectomy patients ( Wang et al , 2018 ) and in bone marrow-derived macrophages induced by LPS ( de Oliveira et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that Gln protected cells against oxidative stress by scavenging free radicals (X. H. Zhou, Wu, et al, 2012). Gln is a precursor for synthesis of glutathione (GSH) which is the most important antioxidant and free radical scavenger (M. H. Kim & Kim, 2017; X. Y. Wang et al, 2018). Furthermore, GSH‐Px can specifically catalyse GSH to scavenge oxygen free radicals and protect cells against oxidative stress (Aquilano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several publications observed an increase in Th1 cytokines (IL-2 and IFN-γ) in PMACI-treated intestinal intraepithelial lymphocytes by glutamine 33 . Similarly, IL-1 and IL-10 were upregulated in glutamine-treated lobectomy patients 32 . Other supplements, such as sodium pyruvate in IMDM, have been shown to impair cytokine production by inhibiting inflammatory signalling pathways 34 .…”
Section: Cell Source and Culture Conditions Of Hmc-1 Cell Linementioning
confidence: 91%
“…Coëffier et al (2001) demonstrated the reduction in pro-inflammatory cytokines (IL-6 and IL-8) from human intestinal mucosa by glutamine via a post-transcriptional pathway 30 . Glutamine has also decreased the expression of leukotriene C 4 , monocyte chemoattractant protein (MCP), macrophage inflammatory protein (MIP)-1β, tumor necrosis factor alpha (TNF-α), interleukin (IL)-15, and IL-18 in human intestinal mast cells, and lobectomy patients 31,32 . In contrast, several publications observed an increase in Th1 cytokines (IL-2 and IFN-γ) in PMACI-treated intestinal intraepithelial lymphocytes by glutamine 33 .…”
Section: Cell Source and Culture Conditions Of Hmc-1 Cell Linementioning
confidence: 99%